Effects of a diet supplemented with polysaccharides from Pogostemon cablin on growth performance, meat quality, and antioxidant capacity in Chongren Partridge chickens - Tang, Yantian; Chen, Si; Chen, Lingli; Ouyang, Kehui; Chen, Hui; Wang, Wenjun (Frontiers in Veterinary Science, 2024)
Various plant polysaccharides are used as feed additives to fortify animal health and improve the nutritional value of derived meat. This study aimed to investigate the effects of the dietary supplementation with different doses of Pogostemon cablin polysaccharides (PCP) on growth performance, meat quality, and antioxidant capacity in Chongren Partridge chickens. The finding indicated that PCP might be considered as a new additive to improve the health and meat quality of Chongren Partridge chickens.